INCREASED LEVETIRACETAM CLEARANCE IN PREGNANCY: IS SEIZURE FREQUENCY AFFECTED?. (29th November 2012) - Hoeritzauer, A; Mawhinney, E; Irwin, B; Hunt, S; Morrow, J; Craig, J
Abstract : Background: Emerging data on the teratogenic potential of valproate and topiramate have resulted in a prescribing shift towards lamotrigine and levetiracetam in women of childbearing age with epilepsy. However use of these AEDs during pregnancy is associated with new difficulties. It is widely documented that lamotrigine clearance increases by up to 330% in pregnancy, with associated increase in seizure frequency in 39–45% of women. Early studies show that levetiracetam serum levels also fall by 40–62% during pregnancy, but in contrast to lamotrigine very little is known about the clinical effect of this observation. Methods: Retrospective chart review was performed for women in Northern Ireland taking levetiracetam monotherapy during pregnancy from 2003 to 2011. Results: Forty four women taking levetiracetam during pregnancy were identified. Deterioration or relapse of seizures was observed in 30.8% of women, improvement in seizure control in 17.9% and no change in 51.3%. Conclusion: Seizure control deteriorated in over 30% of women in this study, towards the upper end of the expected range of 14–32%. This is the largest study to date of seizure control in women taking levetiracetam during pregnancy. These preliminary findings, together with the paucity of evidence in this area, highlight that further research is clearly needed to guide clinicians on the potential clinical impact of this phenomenon.